The Art of Teaching Classical Ballet Book review (Dance Books Ltd., Alton,Hampshire (UK), 1998)
The issue of conflicting training methods. PALABRAS CLAVE: teaching, classical ballet.
The Art of Teaching Classical Ballet. Woytek Lowski, Dance Books, 1998.